2019
DOI: 10.3390/nu11030527
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Sustained Plasma Concentrations of CoQ10 in Healthy Volunteers by a Novel Oral Timed-Release Preparation

Abstract: Coenzyme Q10 (CoQ10) is a natural compound with potent antioxidant properties. Its provision through diet does not always allow adequate levels in the human body, and supplementation is often necessary. This bioavailability study intended to explore the plasma concentration levels of a novel CoQ10 oral preparation (COQUN®, Coenzyme Q10 Miniactives Retard 100 mg capsules) mimicking assumption on a regular basis. Twenty-four healthy adults tested a single dose of CoQ10 100 mg in one day to assess bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…These efforts have been focused on reductions in its particle size and the modulation of its water solubility/dispersibility, e.g., using complexation, solubilization, or reduction [3]. In a recent study, very promising results using modified-release preparations were also reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have been focused on reductions in its particle size and the modulation of its water solubility/dispersibility, e.g., using complexation, solubilization, or reduction [3]. In a recent study, very promising results using modified-release preparations were also reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of our study was that there is no negative control, i.e., meals alone. In the previous reports, there was no placebo control for the determination of the absorption/bioavailability of CoQ 10 supplements [25][26][27][52][53][54][55]. Also, the effect of CoQ 10 contents in the provided meals seemed to be extremely low as the estimated CoQ 10 amount was less than one two-hundredth of the CoQ 10 supplements ingested.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the low concentration of coenzyme Q10 in melanoma cell lines, and in sera of patients with melanoma, CoQ10 was used in combination with an optimized dose of recombinant interferon α-2b in a 3-year trial, which demonstrated that this combination significantly reduced the recurrence rate ( 79 ). A recent study reported that the mean of maximum plasma concentration in a group of healthy volunteers who received 100 mg (Bid) of CoQ10 was 1501 µg/l (1.8 µM) ( 80 ). It is also known that 300 mg per day is a common dosage of commercial products of coenzyme Q10 ( 81 ).…”
Section: Discussionmentioning
confidence: 99%